Episodic versus Chronic Dizziness: An Analysis of Predictive Factors. (April 2022) - Formeister, Eric J.; Chae, Ricky; Wong, Emily; Chiao, Whitney; Pasquesi, Lauren; Sharon, Jeffrey D.
Objectives: To elucidate differences in demographic and clinical characteristics between patients with episodic and chronic dizziness. Methods: A cross-sectional, observational study of 217 adults referred for dizziness at 1 tertiary center was undertaken. Subjects were split into a chronic dizziness group (>15 dizzy days per month) and an episodic dizziness group (<15 dizzy days per month). Results: 217 adults (average age, 53.7 years; 56.7% female) participated. One-third (n = 74) met criteria for chronic dizziness. Dizziness handicap inventory (DHI) scores were significantly higher in those with chronic dizziness compared to those with episodic dizziness (53.9 vs 40.7; P < .001). Comorbid depression and anxiety were more prevalent in those with chronic dizziness (44.6% and 47.3% vs 37.8% and 35.7%, respectively; P > .05). Abnormal vestibular testing and abnormal imaging studies did not differ significantly between the 2 groups. Ménière's disease and BPPV were significantly more common among those with episodic dizziness, while the prevalence of vestibular migraine did not differ according to chronicity of symptoms. A multivariate regression that included age, sex, DHI, history of anxiety and/or depression, associated symptoms, and dizziness triggers was able to account for 15% of the variance in the chronicity of dizziness (pseudo- R 2 = 0.15; P < .001). Conclusions: Those who suffer from chronic dizziness have significantly higher DHI and high comorbid rates of depression and anxiety than those with episodic dizziness. Our findings show that factors other than diagnosis alone are important in the chronification of dizziness, an observation that could help improve on multimodal treatment options for this group of patients.